The gingerbread man (with difficult word-meaning) (Children Publication Karachi, 2012)
his classic tale, adapted into Urdu, tells the story of a gingerbread man who comes to life and runs away from the baker. The story is filled with exciting escapes and narrow misses as the gingerbread man outruns various animals and people. Along with the engaging narrative, the Urdu version of this story can introduce readers to new and challenging vocabulary, providing an opportunity to expand their language skills.